Investigation of the Occurrence of Zoonotic Intestinal Parasites along the Karmanasa River Bank in Lalitpur, Nepal - Roshan Babu Adhikari; Diksha Ghimire; Tirth Raj Ghimire (Veterinary Medicine and Science)
ABSTRACT Introduction Increasing urbanization has particularly affected rivers and their outer edges in cities, including Kathmandu Valley, which encompasses Lalitpur, the nation's third‐largest city. This study aims to conduct a parasitological survey to investigate the occurrence of zoonotic intestinal protozoa and helminths along the Karmanasa River bank in central Nepal. Methods Faecal samples from openly defaecating animals were collected via non‐invasive techniques, and coproscopy was carried out using direct wet mount, concentration and acid‐fast staining methods to ensure reliable findings. Results The findings showed that all the faecal samples were positive for intestinal parasites as follows: buffaloes (15/15), cats (5/5), cattle (30/30), chickens (7/7), dogs (15/15), goats (15/15), pigs (20/20) and rats (12/12). A total of 28 intestinal parasites were reported, out of which 21 species possess zoonotic potentialities, and each host was reported to harbour at least one zoonotic parasite. Entamoeba sp., Cryptosporidium sp., hookworm, Trichuris sp., Trichostrongylus and Balantidium coli were among the predominant zoonotic parasites. The use of the landscape for livestock grazing and the presence of free‐ranging animals could have all added to the zoonotic risks. Moreover, the excretion of a moderate to large number of zoonotic parasite eggs in the faecal samples indicates a transmission risk. Conclusions The study detected 21 species of intestinal zoonotic parasites circulating along the landscape in the study area, indicating a higher risk of cross‐transmission. Therefore, strategic treatment of livestock and free‐ranging animals and periodic public health awareness programs for the local inhabitants are highly recommended.